2005
DOI: 10.1152/ajpcell.00365.2004
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional properties of four slow skeletal troponin T isoforms in rat muscles

Abstract: We investigated the expression and functional properties of slow skeletal troponin T (sTnT) isoforms in rat skeletal muscles. Four sTnT cDNAs were cloned from the slow soleus muscle. Three isoforms were found to be similar to sTnT1, sTnT2, and sTnT3 isoforms described in mouse muscles. A new rat isoform, with a molecular weight slightly higher than that of sTnT3, was discovered. This fourth isoform had never been detected previously in any skeletal muscle and was therefore called sTnTx. From both expression pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…However, our immunoblot analysis demonstrate that the slow skinned fibers used in functional experiments expressed only slow isoforms of regulatory proteins as previously reported [34], [35]. Thus, only the increase in slow MLC2 O-GlcNAcylation might be related to the modifications in calcium activation properties observed in hyperglycosylated fibers.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, our immunoblot analysis demonstrate that the slow skinned fibers used in functional experiments expressed only slow isoforms of regulatory proteins as previously reported [34], [35]. Thus, only the increase in slow MLC2 O-GlcNAcylation might be related to the modifications in calcium activation properties observed in hyperglycosylated fibers.…”
Section: Discussionsupporting
confidence: 78%
“…Concerning TnT, there are several isoforms presenting a molecular weight from 31 to 36 kDa. In whole protein extract, three slow isoforms (panel B) are resolved and assigned as previously described [34], [35]. In the fraction of proteins retained by RL-2 antibody (lane 2), the sTnT1 was clearly revealed, as well as sTnT2, while no signal was detected for sTnT3.…”
Section: Resultsmentioning
confidence: 95%
“…In rat, rabbit, and human muscles, two isoforms (TnT1s and TnT2s) have been identified in slow fibers (249,691,716). Three slow splicing variants (sTnT1, sTnT2, and sTnT3) were described in mouse muscles, and a new variant, with a molecular weight slightly higher than that of sTnT3, was found in rat muscles (414).…”
Section: Response Of Myofibrils To Calciummentioning
confidence: 99%
“…Differently expressed isoforms of proteins are the basis of muscle heterogeneity inherent to soleus and gastrocnemius muscles [10,15,[25][26][27]]. In the current study, this was shown by the variation in the relative abundances of MLC isoforms and metabolic enzymes as well as in the presence of parvalbumin in the white portion of gastrocnemius muscle [28].…”
Section: Discussionmentioning
confidence: 54%